2017
DOI: 10.1039/c7tb00311k
|View full text |Cite
|
Sign up to set email alerts
|

Protein-repellent and antimicrobial nanoparticle coatings from hyaluronic acid and a lysine-derived biocompatible surfactant

Abstract: Biofilm formation triggered by uncontrolled protein adsorption, on medical devices is the leading cause of catheter-associated urinary tract infections (CAUTI) during implantation. Herein, we report a water-based, green and one-step strategy to functionalize surfaces of silicone catheters, poly(dimethylsiloxane) (PDMS), with antifouling and antimicrobial substances to avoid uncontrolled protein adsorption and microbial attachment. A novel synergetic formulation consisting of an anionic glycosaminoglycan (hyalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…This shows that the adsorbed nanolayers substantially reduced the hydrophobicity of PDMS due to the introduction of polar and charged groups. 14 , 15 , 31 However, the obtained SCA(H 2 O) of the two functionalized samples are on the edge of hydrophobicity and appear more hydrophilic.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This shows that the adsorbed nanolayers substantially reduced the hydrophobicity of PDMS due to the introduction of polar and charged groups. 14 , 15 , 31 However, the obtained SCA(H 2 O) of the two functionalized samples are on the edge of hydrophobicity and appear more hydrophilic.…”
Section: Resultsmentioning
confidence: 97%
“…41 nm) with less incorporated water, followed by the formation of a more swollen or hydrated top layer as the adsorption continued. 14 , 31 , 35 , 36 On the contrary, for Chi-77KS/AMOX, a steady increase in dissipation and a steep slope are observed, suggesting the formation of more loosely adsorbed layers ( ca. 61 nm) on the PDMS surface with more incorporated water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of amino acid derivatives belonging to the negatively charged amino acid class are exemplified herein by arginine-containing amphiphilic compounds documented as additives for modification of physicochemical properties of oil [ 39 ], potential antimicrobial compounds active against Micrococcus luteus , Bacillus subtilis , Staphylococcus aureus strains [ 40 ] and agents capable to bind with heparin [ 41 ], which activity could be regulated by selecting appropriate alkyl tail length for the amphiphile. Compositions based on amphiphilic lysine derivatives were documented as drug delivery vehicles containing encapsulated 5-fluorouracil [ 42 ] for cancer treatment as well as the component for design of coating against protein adsorption on nanoparticles [ 43 ]. In [ 44 ] promising stimuli-responsive double-tailed lysine-based surfactants were obtained.…”
Section: Self-assembly Of Amphiphilic Compoundsmentioning
confidence: 99%
“…Another interesting study carried out by Bracic et al . explored the immobilization of PNPs composed by hyaluronic acid and a lysine-derived biocompatible cationic surfactant in silicone catheters to evaluate their efficacy against five different colonizing bacteria of urinary tract medical devices [ 109 ]. In this case, obtained results revealed that that the microbial growth is hampered almost by 85% compared to unmodified silicone catheters.…”
Section: Recent Polymeric Nanoparticles Against Most Common Human Bacmentioning
confidence: 99%